Implant-Related Complications Do Not Interfere with Corrections with the Shilla Technique in Early Onset Scoliosis: Preliminary Results - Mehmet Bülent Balioğlu; Kadir Abul; Ahmet Onur Akpolat; Ali Volkan Özlük; Nurullah Saçık; Mehmet Fatih Aksay; Mehmet Çetinkaya (MDPI AG, 2023)
Growth-preservation techniques are utilized in early onset scoliosis (EOS) cases requiring surgical intervention. The Shilla technique corrects the deformity by reducing additional surgeries with its growth-guidance effect. As with other techniques, various problems can be encountered following the administration of the Shilla technique. The aim of this study was to examine the effect of complications encountered with the Shilla treatment on correction and growth. Sixteen patients with a follow-up period of at least one year after receiving Shilla growth guidance for EOS were included in this retrospective study. No complications occurred, and no unplanned surgery was required in 50% of the cases. Of the remaining eight patients with postoperative implant-related complications (50%), six (37.5%) required unplanned surgery; this consequently caused implant failure in the proximal region in five cases (31.25%) and deep tissue infection around the implant in one case (6.25%). Deformity correction, spine length, and quality-of-life scores significantly improved in EOS through Shilla growth guidance. In terms of spinal growth and deformity correction, there were no significant differences between patients with implant-related problems and individuals without occurrences. Although implant-related problems were detected in our dataset and corresponding unexpected surgeries were necessary, these complications had no significant unfavorable influence on correction and spine growth.